Analysis of the Hall‐effect data on Mn‐doped GaAs with taking into account the Hall factor for nearest‐neighbor hopping conduction. Issue 5 (2nd May 2016) - Kajikawa, Yasutomo
Abstract: The experimental data of the temperature‐dependent Hall‐effect measurements on Mn‐doped p ‐GaAs reported by Wolos et al. [Phys. Status Solidi C6, 2769 (2009)], which exhibit the characteristic of nearest‐neighbor hoping (NNH) conduction, have been analyzed. For NNH conduction, it is assumed that the conductivity is expressed as σib ( T ) ∝︁ T −3/2 exp(− T 0 / T ) while the Hall factor is expressed as Aib ( T ) ∝︁ T exp(− T 0 H / T ), where T 0 and T 0 H are adjustable parameters. It is found that kB T 0 increases from 9 to 21 meV in proportion to the cube root of the substitutional Mn acceptor concentration, being consistent with the theory for NNH conduction. It is also found that K NNH = T 0 H / T 0 decreases from 1.45 to 1.15 with increasing the substitutional Mn acceptor concentration from 0.8×10 17 to 4×10 17 cm ‐3, being different from the concentration‐independent value of K NNH = 2/3 or 1/6 predicted by the theories. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)